(untitled) (KEMANUSIAAN The Asian Journal of Humanities, 2023)
Ruskin Bond is a well-known Indian author whose works are deeply rooted in his personal experiences and observations. His stories often feature an autobiographical element, with characters and settings inspired by his own life. This study explores the autobiographical element in Bond’s writings and how it adds depth and authenticity to his works. Through an analysis of some of his famous short stories, the researchers highlight how Bond’s stories reflect his experiences of growing up in small towns in India, observing people at railway stations, spending time with local craftsmen and living in the Himalayas. The researchers also discuss how Bond’s works often explore themes of individuality, simplicity, nostalgia and the relationship between humans and nature. Overall, Bond’s autobiographical element brings a unique perspective to his works and captures the essence of human relationships and the importance of finding beauty and joy in the everyday.